Associations between vegetative and production traits in guava tree full-sib progenies - Santos, Paulo Ricardo dos (2017)
The objective of this work was to estimate the genetic parameters and to evaluate the associations between vegetative and yield characteristics, in full-sib progenies of guava tree (Psidium guajava). The following characteristics were evaluated: yield per plant, number of fruits, fruit mass, plant height, stem diameter, and canopy volume. The estimation of genetic parameters was obtained by the REML/Blup procedure. Based on the breeding values predicted by Blup, the genetic and canonical correlations were estimated, and the genetic correlation coefficients were unfolded into direct and indirect effects on the character yield per plant using path analysis. Genetic variability was estimated for number of fruits (567.66) and yield per plant (11.818), with high genetic correlation (0.9045), indicating simultaneous selection. Indirect selection did not promote simultaneous gains for yield per plant with the primary components number of fruits and fruit mass, making it difficult to obtain guava cultivars with high yield, number of fruits, and fruit mass. The vegetative traits had little effect on yield, number of fruits, and fruit mass.